Character Based Management Bina Pribadi Islami (BPI) - Sutrimo, Sutrimo; Eko Pramono, Suwito; Made Sudana, I (Educational Management, 2021)
This study aims to determine the planning, implementation, and evaluation of BPI learning activities at SDIT Nurul Islam Tengaran. The development of character values in schools is a barometer of the success of character education. SDIT Nurul Islam Tengaran is one of the Islamic schools that prioritize Islamic character values with the Islamic Personal Development (BPI) program. This research approach is qualitative in the form of case studies. Data were obtained by means of observation, interviews, and document studies. The data that has been collected is then analyzed using qualitative analysis, in which the research results will be translated into words so that researchers can describe the research results in depth according to the actual conditions in the field. The results of the research at SDIT Nurul Islam Tengaran show that the management of BPI based on character education includes: (1) planning with the stages of the process: determining the BPI team from class teachers and subject teachers, compiling BPI SOPs in learning, preparing online, blended schedules and offline mode, BPI implementation strategy, and determination of BPI material in accordance with SKL JSIT Indonesia (2) implementation in the form of socialization of the BPI program to teachers, students and parents as well as various strategies during the pandemic and (3) evaluation in the form of Process evaluation and evaluation of results.